The Implementation of Artificial Intelligence in Islamic Religious Education: An Analysis of Its Impact on Students’ Religious Moderation Literacy at SMA 8 Bungo - Sovia Alacuba; Siti Khamim; Wiwin Narti; Sugeng Kurniawan; Ulfa Adilla (The Future of Education Journal, 2023)
The integration of Artificial Intelligence (AI) into Islamic Religious Education (IRE) offers significant potential for pedagogical transformation; however, its empirical impact on students’ religious moderation literacy remains underexplored. This study aims to analyze the level of AI implementation in Islamic Religious Education and its impact on the religious moderation literacy of students at SMA 8 Bungo. The research employed an explanatory sequential mixed-methods design involving students from Grades X–XII as the study population. Quantitative instruments included a religious moderation literacy scale adapted from the indicators developed by the Indonesian Ministry of Religious Affairs (2021) and a questionnaire measuring AI adoption in Islamic Religious Education. These instruments were complemented by in-depth interviews and participant observations. Quantitative data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS), while qualitative data were examined through thematic analysis. The findings indicate that the level of AI implementation was categorized as moderate to high (M = 3.82, SD = 0.61). AI implementation had a positive and significant effect on students’ religious moderation literacy (β = 0.412, p < 0.001), particularly in the dimensions of tolerance, national commitment, and anti-violence attitudes. Qualitative findings revealed that AI facilitated cross-school-of-thought exploration, contemporary case-study simulations, and personalized value reflection. Nevertheless, challenges remained, including digital access disparities and insufficient teacher training in AI-based content curation. The study recommends the development of verified AI-integrated Islamic Religious Education modules, digital pedagogical training for teachers, and school policies that support ethical technology-based learning ecosystems.